Analys och förslag på förbättringar av röntgenprocessen på Skaraborgs sjukhus - Andersson, Alice; Halvarsson, Josefin (My University, 2022)
Swedish healthcare is facing many challenges, such as long waiting times as a result of a growing elderly population and an increased need for care which has caused a capacity deficit in healthcare. The growing medical demand requires increased medical measures, thus a solution is to improve the efficiency of the care process to meet the growing demand. The radiology department is one of the medical processes where the queue is growing and is also a shared, critical resource for most patient flows. Computed tomography examinations make up 30% of all examinations performed at Skaraborgs sjukhus. The capacity of the radiology department is insufficient to meet the existing need and approximately 25% of patients in need of computed tomography examinations is not provided with care in time. Thus, it is considered important to improve the efficiency of the computed tomography process in order to provide patients with the right care in time. The aim of this thesis was to describe the current radiology process and identify the largest areas where the capacity can be improved. Furthermore, the identified areas were the basis of the analysis aimed at presenting improvement proposals regarding how Skaraborgs sjukhus can increase capacity with existing resources. The study has been carried out at the division in charge of scheduling patients appointments and at the radiology unit working with nonemergency patients. Primary data has been collected through observations and interviews. Secondary data regarding previously performed examinations have also been analyzed to achieve the purpose of the thesis. The thesis found a number of areas where the capacity could be improved within the radiology process. The work of the scheduling division was found to be affected mainly by external factors. The main areas of improvements in the radiology unit were lack of routines of registrations and variation in examination time as a result of preparations varying in time. Based on the areas of improvements described above, the following improvement proposals were developed. A suggestion is to introduce standardized work methods for registration of start- and end times of examinations and further focus on flow efficiency. Moreover, a proposition is to move the work associated with changeover and set up time to a separate room. The proposed improvements are expected to contribute to an increased efficiency of the radiology process, however, it is uncertain if the improvements can be carried out with existing resources.
Keywords: process theory, radiology, flow efficiency, healthcare.